Pemberdayaan Masyarakat Terhadap Limbah Rumah Tangga Organik Dengan Teknik Komposter - Ratu Eva Ferbriani; Retno Agustina Ekaputri; Mochammad Ridwan (UNIB Press, 2022)
Household waste is the most common type of waste produced as a side effect of human activities. In its development, the handling of this waste problem cannot only rely on the government but there needs to be another alternative in the form of community empowerment in managing household waste through the application of composter techniques. By using a composter, besides reducing waste generation, it also helps maintain the capacity of the landfill and can create new sources of income for households. This service activity aims to educate the public about waste and its processing. The locus of this activity is RT 05 Bentiring Village, Bengkulu City, using the extension method. This community service activity has succeeded in changing the community's paradigm in managing household waste and encouraging the application of composting techniques at home.